Separation of oil and water by using coconut coir - Aimuni Izzati, Mohammad Yatim (2012)
The aims for this study are to examine the emulsion stability and to evaluate the effectiveness of using coconut coir in the separation of oil and water (emulsion).Crude oil and distilled water were used as the raw materials.To complete the objective,there are three main (3) parts of experiment need to be done.The first part was the pretreatment of the coconut coir.In this part,the required particle sizes of the coir which varied between 630 µm to 2 mm were determined and also had been modified,weighing and packaging.While in the second part the formation and stabilization of the oil-inwater (O/W) emulsion was examined.The O/W ratios were varied from 50-75:50-25 and during the stability part the emulsion was verified by visually observes on separation layer for each of the samples of emulsion.As for the emulsifier, Tween 20 at different concentration 1%,3% and 5% of total volume was used in formation of O/W emulsion.Last but not least,the last part studied the separation of oil and water by using coconut coir.The optimum condition of O/W emulsion is discovered by the correlation between the emulsifier concentrations,and oil-water ratio. Here,the effectiveness of prepared coconut coir is analyzed in order to adsorbed the raw crude oil,and water by considering the effect of size particles and the modification of the coconut coir. Then,the amount of oil and water being adsorbed and recover from the coconut coir are weighed to see the efficiency of the coconut coir.The most stable of O/W emulsion was found at 5% of emulsifier concentration at 75-25% of oil-water ratio.The adsorption of oil was better at 630µm particle size of unmodified coir.Therefore,the effectiveness of the coconut coir in order to separate the most stable emulsion into oil and water would be required.